Lewy body diseases and the gut - Timothy R. Sampson; Malú Gámez Tansey; Andrew B. West; Rodger A. Liddle (Molecular Neurodegeneration)
Abstract Gastrointestinal (GI) involvement in Lewy body diseases (LBDs) has been observed since the initial descriptions of patients by James Parkinson. Recent experimental and human observational studies raise the possibility that pathogenic alpha-synuclein (⍺-syn) might develop in the GI tract and subsequently spread to susceptible brain regions. The cellular and mechanistic origins of ⍺-syn propagation in disease are under intense investigation. Experimental LBD models have implicated important contributions from the intrinsic gut microbiome, the intestinal immune system, and environmental toxicants, acting as triggers and modifiers to GI pathologies. Here, we review the primary clinical observations that link GI dysfunctions to LBDs. We first provide an overview of GI anatomy and the cellular repertoire relevant for disease, with a focus on luminal-sensing cells of the intestinal epithelium including enteroendocrine cells that express ⍺-syn and make direct contact with nerves. We describe interactions within the GI tract with resident microbes and exogenous toxicants, and how these may directly contribute to ⍺-syn pathology along with related metabolic and immunological responses. Finally, critical knowledge gaps in the field are highlighted, focusing on pivotal questions that remain some 200 years after the first descriptions of GI tract dysfunction in LBDs. We predict that a better understanding of how pathophysiologies in the gut influence disease risk and progression will accelerate discoveries that will lead to a deeper overall mechanistic understanding of disease and potential therapeutic strategies targeting the gut-brain axis to delay, arrest, or prevent disease progression.